2016
DOI: 10.1016/j.actbio.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Influencing chondrogenic differentiation of human mesenchymal stromal cells in scaffolds displaying a structural gradient in pore size

Abstract: We present the development of a novel hierarchical scaffold obtained by additive manufacturing. Structural hierarchy is obtained by changing pore size within the pore network characterizing the fabricated scaffolds and proves to be a functional element in the scaffold to influence adult stem cell differentiation in the chondrogenic lineage. Specifically, in regions of the scaffolds presenting smaller pores an increasing differentiation of stem cells toward the chondrogenic differentiation is displayed. Taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 47 publications
(50 reference statements)
0
71
0
1
Order By: Relevance
“…One group has recently demonstrated that gradient pore sizes created by FDM can slightly improve both chondrogenesis 49 and osteogenesis 48 , although they did not investigate different geometries. By designing scaffold pore sizes and geometries based on biological mechanical requirements, these improvements may be further enhanced.…”
Section: 3d Printing For Craniofacial Bone Regenerationmentioning
confidence: 99%
“…One group has recently demonstrated that gradient pore sizes created by FDM can slightly improve both chondrogenesis 49 and osteogenesis 48 , although they did not investigate different geometries. By designing scaffold pore sizes and geometries based on biological mechanical requirements, these improvements may be further enhanced.…”
Section: 3d Printing For Craniofacial Bone Regenerationmentioning
confidence: 99%
“…Different pore size gradients revealed stimulation of different cell behaviors. In this sense, the authors showed the capability to tune the scaffolds' architecture using FDM to achieve an improved induction of mesenchymal stem cells chondrogenesis and osteogenesis [34,35].…”
Section: Fused Deposition Modelingmentioning
confidence: 99%
“…The goal was to enhance cell seeding efficiency and control the spatial organization of cells within the scaffold. Some authors [22] also emphasized the importance of scaffold pore size gradients in osteogenic differentiation of human mesenchymal stromal cells. In 2010, Puppi et al [23] in deep reviewed the design of biodegradable and bioactive polymeric scaffolds, with properly suited architecture and tailored properties for bone and cartilage tissue regeneration.…”
Section: Scaffold Designmentioning
confidence: 99%